Green synthesis of silver nanoparticles using Sago (Metroxylon Sagu) via auto claving method - Aliyah, Jamaludin; Che Ku Mohammad Faizal, Che Ku Yahya (IIUM, Malaysia, 2018)
Sago (metroxylon sagu) is a polysaccharide bio resource, which is biodegradable and low in toxicity that can be found in large scale in Mukah, Sarawak. A simple green method of synthesizing silver nanoparticles (AgNPs) has been developed using sago dissolved in water as the reducing agent. The mixture of dissolved sago and silver nitrate (AgNO3) were autoclaved at 121 °C for 20 minutes. The size, morphology and structures of the AgNPs formed in the sago solution were investigated through UVVis spectrophotemeter, XRD and FESEM analysis. The synthesized AgNPs were spherical in shape and well distributed with average particle sizes of 19.3 ± 2.7 nm